QoS-Aware Routing Mechanism in OpenFlow-Enabled Wireless Multimedia Sensor Networks - Li Han; Shimin Sun; Bokgyu Joo; Xianshu Jin; Sunyoung Han (International Journal of Distributed Sensor Networks)
Applications supporting various multimedia data in wireless multimedia sensor networks (WMSNs) have specific QoS requirements on bandwidth, delay, and/or packet loss. Perception of applications' QoS requirements and detection of link states are indispensable for the design of QoS-aware routing mechanism. Software defined networking (SDN) is suitable for the purpose since it provides visibility of network resources and programmable interfaces. OpenFlow is the most recognized realization of SDN. We propose a QoS-aware routing mechanism for OpenFlow-enabled WMSNs. The mechanism consists of a framework and routing algorithms on SDN controller. The framework includes two functions: detection of link states among OpenFlow-enabled nodes and determination of flow's QoS requirements. The routing algorithms are achieved in two steps. First, the SDN controller seeks the feasible paths that satisfy QoS requirements of a flow. If there is no path which satisfies the required QoS, the path will be decided by the proposed algorithms depending on flow types: delay-sensitive, bandwidth-sensitive, and best-effort traffic. We conducted experiments on a SDN testbed to evaluate our mechanism and compared the results with conventional routing protocols. The results show that proposed routing mechanism increases the throughput by 43% for video data and reduces the delay by more than 30% for audio data.